Experimental analysis of the Schottky barrier height of metal contacts in black phosphorus field-effect transistors. (8th March 2018) - Chang, Hsun-Ming; Fan, Kai-Lin; Charnas, Adam; Ye, Peide D; Lin, Yu-Ming; Wu, Chih-I; Wu, Chao-Hsin
Abstract: Compared to graphene and MoS2, studies on metal contacts to black phosphorus (BP) transistors are still immature. In this work, we present the experimental analysis of titanium contacts on BP based upon the theory of thermionic emssion. The Schottky barrier height (SBH) is extracted by thermionic emission methods to analyze the properties of Ti-BP contact. To examine the results, the band gap of BP is extracted followed by theoretical band alignment by Schottky–Mott rule. However, an underestimated SBH is found due to the hysteresis in electrical results. Hence, a modified SBH extraction for contact resistance that avoids the effects of hysteresis is proposed and demonstrated, showing a more accurate SBH that agrees well with theoretical value and results of transmission electron microscopy and energy-dispersive x-ray spectroscopy.